Uniwersalia a przedmioty ogólne - Kaczmarek, Janusz (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2005)
In the paper we treat one of the most hotly debated and still current topics in ontology i.e. the problem of universals. By two formal representations of incomplete and complete objects we argue that only genera and species (as counterparts of Aristotle's Forms and Plato's Ideas) are universals. They only are what is called nature or essence of individuals named by general terms. On the contrary, although the concepts are second kind of objects signified by general terms, they have another status as complete objects. Hence, in that meaning "generality" stick in two different kind of objects – in universals and concepts. But being general is not equal to being universal in Aristotle's and Plato's sense.